A new PI optimal linear quadratic state-estimate tracker for continuous-time non-square non-minimum phase systems. Issue 7 (19th May 2017) - Tsai, Jason Sheng-Hong; Liao, Ying-Ting; Ebrahimzadeh, Faezeh; Lai, Sheng-Ying; Su, Te-Jen; Guo, Shu-Mei; Shieh, Leang-San; Tsai, Tzong-Jiy
ABSTRACT: Based on the proportional-integral-derivative (PID) filter-shaping approach, this paper presents a new proportional-plus-integral (PI) optimal linear quadratic state estimator (LQSE) for the continuous-time non-square and non-minimum phase (NMP) multivariable systems. Together with the recently developed optimal linear quadratic tracker (LQT), the proposed LQSE-based tracker is able to optimally achieve good minimum phase-like tracking performances for a non-square NMP multivariable system with unmeasurable states and arbitrary command inputs.